Development of a single-phase PWM AC controller - Bashi, Sinan Mahmod; Mailah, Nashiren Farzilah; Cheng, Wong Bong (Universiti Putra Malaysia Press, 2008)
An AC chopper controller with symmetrical Pulse-Width Modulation (PWM) is proposed to achieve better performance for a single-phase induction motor compared to phase-angle control line-commutated voltage controllers and integral-cycle control of thyristors. Forced commutated device IGBT controlled by a microcontroller was used in the AC chopper which has the advantages of simplicity, ability to control large amounts of power and low waveform distortion. In this paper the simulation and hardware models of a simple single phase IGBT An AC controller has been developed which showed good results.